Evaluation of non-invasive biomonitoring of 2, 4-Dichlorophenoxyacetic acid (2, 4-D) in saliva. (1st December 2018) - Carver, Zana A.; Han, Alice A.; Timchalk, Charles; Weber, Thomas J.; Tyrrell, Kimberly J.; Sontag, Ryan L.; Luders, Teresa; Chrisler, William B.; Weitz, Karl K.; Smith, Jordan N.
Abstract: The objective of this study was to evaluate the potential for non-invasive biomonitoring of 2, 4-Dichlorophenoxyacetic acid (2, 4-D) in saliva. Using an in vitro rat salivary gland epithelial cell (SGEC) system, a collection of experiments investigating chemical protein binding, temporal and directional transport, as well as competitive transport with para-aminohippuric acid (PAH), a substrate for renal organic anion transporters, was conducted to identify cellular transport parameters required to computationally model salivary transport of 2, 4-D. Additionally, a physiological protein gradient was implemented to mimic physiologically relevant concentrations of protein in rat plasma and saliva, and under these conditions the transfer of 2, 4-D was markedly slower, driven by increased protein binding ( i.e. reduced free 2, 4-D species available to cross salivary barrier). The rate of transfer was directly proportional to the amount of unbound 2, 4-D and demonstrated no indication of active transport. An in vivo assessment of 2, 4-D exposure in rats revealed non-linear protein binding in plasma, indicating saturated protein binding and increased levels of unbound 2, 4-D species at higher doses. A strong correlation between 2, 4-D concentrations in saliva and unbound 2, 4-D in plasma was observed (Pearson correlation coefficient = 0.95). Saliva:plasma 2, 4-D ratios measured in vivo (0.0079) were consistent within the linear protein binding range and expected 2, 4-D levels from occupational exposures but were significantly different than ratios measured in vitro (physiological conditions) (0.034), possibly due to 2, 4-D concentrations in saliva not being at equilibrium with 2, 4-D concentrations in blood, as well as physiological features absent in in vitro settings ( e.g. blood flow). We demonstrated that 2, 4-D is consistently transported into saliva using both in vitro and in vivo models, making 2, 4-D a potential candidate for human non-invasive salivary biomonitoring. Further work is needed to understand whether current sensor limits of detection are sufficient to measure occupationally relevant exposures.